PENGARUH SENAM LANSIA TERHADAP KUALITAS TIDUR PADA LANSIA YANG INSOMNIA - Famelia ' Yurintika; Febriana ' Sabrian; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This Study aimed to understand the effect of elderly gymnastic on the sleep quality of insomnia elders. This study used “quasi experiment” as the study design with “pre test and post test design with control group design. The study was conducted at Panti Sosial Tresna Wredha Pekanbaru (PSTW). Thirty four people were chosen as the sample using purposive sampling technique while keeping the inclusion criteria on mind. The measurement instruments used on both group were KSPBJ-IRS questionnaire (Kelompok Studi Psikiatri Biologik Jakarta– Insomnia Rating Scale) for insomnia and PSQI (Pittsburgh Sleep Quality Index) for sleep quality. The analyses used were univariate analysis and bivariate analysis using Wilcoxon test and Mann Whitney. The results of this study showed a significant increase on the sleep quality of experiment group after the elderly followed the exercise with P value = (0,000) < α (0,05). Based on this study, health workers are expected to implement this exercise as one the non - pharmalogically way to increase sleep quality on the elderly peolpe. Keywords : Elders, gymnastic, insomnia, sleep quality